2015 Public Expenditure and Financial Accountability of Colombia’s Public Financial Management Systems - World Bank (World Bank, Washington, DC, 2017)
The objective of the 2015 Colombia Public Expenditure and Financial Accountability (PEFA) assessment is to have an updated diagnosis of the performance of the public financial management (PFM) system in the country so as to (i) determine the progress made with the reforms implemented in recent years by the Government of Colombia (GoC), (ii) understand the impacts of these reforms, (iii) establish the tools and next steps necessary to consolidate the progress made, and (iv) promote long-term economic stability and sustainability. The scope of the PEFA Colombia 2015 exercise covers the Central Government and the assessment analysis period are the last three completed fiscal years (2012, 2013, and 2014), at the time of the assessment (December 2015). The field mission took place in Bogota between November 12 and December 18, 2015, and this report was prepared between January 4 and August 17, 2016, incorporating comments from the Government of Colombia and guest reviewers.